2010
DOI: 10.1111/j.2041-210x.2010.00079.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA melting analysis as a tool for species identification

Abstract: Summary 1.One of the ongoing challenges in molecular biology is to develop rapid, accurate and reliable techniques to identify organisms. This contribution evaluates the value of DNA melt peak analysis for the identification of pests and pathogens significant to biosecurity. 2. The method evaluated in this study capitalises on the observation that double-stranded DNA separates into single strands (melts) at a temperature dependant on the nucleotide sequence of the DNA strands. The temperature and shape of melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 43 publications
1
46
0
1
Order By: Relevance
“…The present work describes a primer pair, SalF and SalR, based on the 16S rRNA gene and a high‐throughput SYBR Green I‐based real‐time PCR protocol combined with melting curve analysis as a sensitive, specific and inexpensive method for the identification and quantification of the fish pathogen Vagococcus salmoninarum in bacterial cultures and infected fish tissue homogenates. This qPCR diagnostic‐based method can robustly monitor and quantify amplified products in a single tube in “real time” without the need for electrophoresis gels (Winder et al, ), avoiding post‐processing steps and delays, and minimizing potential experimental error. This assay can be completed in <3 hr, including DNA preparation from bacterial cultures or fish tissues, qPCR amplification and melting curve analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The present work describes a primer pair, SalF and SalR, based on the 16S rRNA gene and a high‐throughput SYBR Green I‐based real‐time PCR protocol combined with melting curve analysis as a sensitive, specific and inexpensive method for the identification and quantification of the fish pathogen Vagococcus salmoninarum in bacterial cultures and infected fish tissue homogenates. This qPCR diagnostic‐based method can robustly monitor and quantify amplified products in a single tube in “real time” without the need for electrophoresis gels (Winder et al, ), avoiding post‐processing steps and delays, and minimizing potential experimental error. This assay can be completed in <3 hr, including DNA preparation from bacterial cultures or fish tissues, qPCR amplification and melting curve analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In SYBR Green qPCR assays, the amount of PCR products (amplicons) can be detected by measuring fluorescence levels from the cycle threshold ( C q ) (Winder et al, ). Therefore, based on the observed values of C q and the linear standard curve generated, the SalF and SalR primers designed in this study showed the highest sensitivity and were estimated to have a detection limit of 0.034 × 10 0 copies of amplicon by μl (equivalent to 2.0 × 10 −11 ng/µl genomic DNA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it may not work well for the HRM analysis in situations when short PCR fragments are amplified as it results in a weak fluorescence emission, yielding small, hard to detect melting peaks. 30-35 Thus, “saturation dyes” such as LC Green Plus, SYTO9, Eva Green, or ResoLight have been developed to be used with the HRM technique. 33,36 These dyes do not inhibit PCR amplification even at concentrations that completely saturate DNA.…”
Section: Discussionmentioning
confidence: 99%
“…They tend to have high sensitivity due to the use of polymerase chain reaction (PCR), high specificity to the chosen target and can be used on highly processed samples, many of which have been exposed to high temperatures [9]. Common DNA techniques using PCR include PCR-restriction fragment length polymorphisms (PCR-RFLP), amplified fragment length polymorphisms (AFLP), forensically informative nucleotide sequencing (FINS), random amplified polymorphic DNA (RAPD), melt curve analyses [10,11] and DNA sequencing [12]. A lack of governance and standardisation relating to species identification in food standards means that each laboratory often develops ad-hoc approaches, many of which have been phased out of use in routine forensic applications.…”
Section: Introductionmentioning
confidence: 99%